The significance of local governments in brownfield redevelopment projects - Molnár Adrienn (2015)
THE SIGNIFICANCE OF LOCAL GOVERNMENTS IN BROWNFIELD REDE-VELOPMENT PROJECTS Az önkormányzatok szerepe a barnamezős fejlődésben In the thesis my purpose was to find out how the local governments can encourage brown-field redevelopment projects, and also the situation of brownfields Hungary and in Fin-land, especially in Várpalota, and Seinäjoki. In order to achieve that, first, I researched in the available professional material and trying to find examples and solutions that the local governments could possibly use to stimulate and support brownfield projects. Furthermore, I used case studies from the USA, Canada, the United Kingdom, and Germany in order to get a closer look to the practical side of brownfield projects. Those showed some excellent examples of collaborations and how the local governments, private investors and the local community can work together effectively if their goals and interests are common. Finally, I conducted my own research in Várpalota, Székesfehérvár, and Seinäjoki, where I interviewed some of the members of the local governments in order to get the most current information about the situation of brownfield projects conducted in those ci-ties.